Antimicrobial peptides in livestock: a review with a one health approach - Robles Ramirez, Oscar; Osuna, Gabriel; Plisson, Fabien; Barrientos-Salcedo, Carolina (Frontiers in Cellular and Infection Microbiology, 2024)
Antimicrobial peptides (AMPs), often referred to as nature's antibiotics, are ubiquitous in living organisms, spanning from bacteria to humans. Their potency, versatility, and unique mechanisms of action have garnered significant research attention. Unlike conventional antibiotics, peptides are biodegradable, adding to their appeal as potential candidates to address bacterial resistance in livestock farming-a challenge that has been under scrutiny for decades. This issue is complex and multifactorial, influenced by a variety of components. The World Health Organization (WHO) has proposed a comprehensive approach known as One Health, emphasizing the interconnectedness of human-animal-environment relationships in tackling such challenges. This review explores the application of AMPs in livestock farming and how they can mitigate the impact of this practice within the One Health framework.